X-men : Apocalypse - Lee, Stan.; McAvoy, James, 1979-; Lawrence, Jennifer (Beverly Hills, California : 20th Century Fox, 2016)
After the re-emergence of the world's first mutant, world-destroyer Apocalypse, the X-Men must unite to defeat his extinction level plan.
Widescreen (2.40:1)./ Originally released as a motion picture in 2016.
Keywords: Action and adventure films; Science fiction films